(untitled) (Journal of the College of Basic Education, 2023)
The Chinese city of Wuhan is the first geographical location for the outbreak of the Corona virus, or the so-called Covid-, which swept the political borders of the geography of countries in 2019 and thus acquired the status of global, and the impact of the Corona virus on people in different forms, and it does not distinguish between nationalities of countries, nor between ages, women and men, and the world lives The horror of this pandemic or epidemic as it is not medically known, and Iraq, the subject of the research, is not isolated from the countries of the world in the face of this epidemic, and several political, social and economic factors have combined, especially since the crisis has put pressure on the living conditions as a result of the partial disruption of economic and social activities, and on this basis this research focuses To study the various dimensions related to health security left by the Corona pandemic because of their paramount importance in influencing the life of the individual in society.